Burger's Medicinal Chemistry and Drug Discovery 2010
DOI: 10.1002/0471266949.bmc156
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Crystal Forms and Cocrystals in Drug Delivery (Crystal Engineering)

Abstract: Active pharmaceutical ingredients, APIs, are most conveniently developed and delivered orally as solid dosage forms that contain a defined crystalline form of an API. This means that the pharmacokinetic profile of a dosage form is at the very least linked to the physicochemical properties of the crystal form that is selected for development. Furthermore, that crystal forms of new chemical entities are novel, lack obviousness, and have utility makes them patentable. Therefore, selection of a specific crystal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 180 publications
1
5
0
Order By: Relevance
“…The hydrate showed the worst IDR, in line with Khankari and Grant 29 , who reported that the solubility and thus the dissolution rates of hydrates are worse than those of the parent forms [29][30][31] .…”
Section: Intrinsic Dissolution Rate and Particle Dissolutionsupporting
confidence: 79%
“…The hydrate showed the worst IDR, in line with Khankari and Grant 29 , who reported that the solubility and thus the dissolution rates of hydrates are worse than those of the parent forms [29][30][31] .…”
Section: Intrinsic Dissolution Rate and Particle Dissolutionsupporting
confidence: 79%
“…A recent review of the scientific and patent literature indicated that there have been at least 10 pharmaceutical cocrystal case studies with PK details reported to date, many of which support that pharmaceutical cocrystals are a viable option to enhance the clinical performance of a poorly soluble API. 17,18 Clearly, pharmaceutical cocrystals represent an opportunity to diversify the number of crystal forms of a given API and in turn fine tune or even customize its physicochemical and PK properties without the formation/breakage of covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceutical cocrystals are also capable of modifying pharmacokinetic (PK) properties. A recent review has summarized the case studies where the effect of cocrystals on the PK profile has been evaluated, many of which support that pharmaceutical cocrystals are a viable option to enhance the clinical performance of a poorly soluble API. Hickey et al reported a pharmacokinetic study on cocrystals and a marketed form (Tergretol) of carbamazepine in dogs which revealed that the cocrystal showed higher plasma levels than Tergretol which contained an anhydrous polymorph of carbamazepine. According to a more recent report by Zaworotko et al, a cocrystal of meloxicam and aspirin was prepared, which enabled an approximately 12-fold decrease in the time required to reach a concentration of 0.51 g/mL in rats compared with pure meloxicam at an equivalent dose.…”
Section: Introductionmentioning
confidence: 99%